Conservative Oxygen Therapy Might be Beneficial to Patients in the Intensive Care Unit. Issue 4 (July 2017) - Pino, Alejandro; Zappetti, Dana
Abstract : Synopsis : In patients admitted to the intensive care unit for 72 hours or longer, conservative oxygen therapy resulted in lower mortality. However, further studies must be conducted to replicate the findings in another study, as this trial was terminated early. Source : Girardis M, Busani S, Damiani E, et al. Effect of conservative vs. conventional oxygen therapy on mortality among patients in an intensive care unit: the oxygen-ICU randomized clinical trial. JAMA 2016; 316:1583–1589.